Dynamic Provisioning of Container Registries in Edge Computing Infrastructures - Roges, Lucas; Ferreto, Tiago (Anais do Simpósio em Sistemas Computacionais de Alto Desempenho (SSCAD); 2023: Anais do XXIV Simpósio em Sistemas Computacionais de Alto Desempenho, 2023)
The emergence of applications with latency-sensitive demands highlighted some limitations of cloud computing and led to the advent of edge computing. Accompanied by challenges such as mobile users and limited resources, this decentralized computing paradigm is frequently associated with container-based virtualization. However, the traditional container registry has significant limitations in properly provisioning container images on edge infrastructures. Consequently, previous authors focused on improving the application provisioning process by modifying this entity. This paper examines previous attempts at decentralizing container registries in edge computing infrastructures. Based on our initial comparison results, we propose a strategy for dynamically provisioning and deprovisioning container registries based on each server’s storage and the infrastructure’s application demands. The final results show that our strategy can optimize resource utilization in the infrastructure, but needs adjustments to reach the lowest overall latency for application users.